Problem Based Learning sebagai Solusi Pembelajaran Sejarah yang Relevan di Abad 21 (Lembag, 2026)
This study aims to examine in depth Problem Based Learning (PBL) as a highly relevant solution for history learning in the 21st century. In the ever-evolving landscape of digital education, history learning is increasingly required to adopt innovative approaches in order to effectively improve student engagement and conceptual understanding. To achieve this goal, this study relies entirely on a systematic literature review method. This article carefully outlines the basic concepts of Problem Based Learning (PBL) from various theoretical and practical perspectives found in scientific literature. Furthermore, it specifically highlights the strong relevance of PBL to the essential characteristics of 21st century history learning, which emphasizes not only mastery of facts but also the development of critical thinking, collaboration skills, and problem-solving abilities. Based on an extensive analysis of various publications, the results of PBL implementation in the context of existing history learning are also discussed, showing the significant potential of this method in developing students' analytical and interpretive abilities. However, the literature review also identified that the implementation of PBL still faces a number of challenges that need to be overcome. In response to these findings, a comprehensive strategy is proposed, based on best practices and recommendations from previous research, to address these challenges.